2007
DOI: 10.1177/0091270006296763
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Saquinavir With Atazanavir or Low‐Dose Ritonavir Administered Once Daily (ASPIRE I) or Twice Daily (ASPIRE II) in Seronegative Volunteers

Abstract: ASPIRE I and II were prospective, 3-way sequential crossover studies in healthy volunteers to compare the safety and pharmacokinetics of saquinavir/ritonavir (SQV/RTV) with saquinavir/atazanavir (SQV/ATV) administered either once daily (QD, ASPIRE I) or twice daily (BID, ASPIRE II). Treatments were separated by 10 days, and pharmacokinetic analyses were performed on days 11, 32, and 53. SQV pharmacokinetics were significantly higher when dosed with RTV compared to ATV (P < .05 for all comparisons). ATV pharmac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…Examples may include variability in the pregnane X receptor (PXR), which controls transcription of CYP3A and ABCB1, the CYP3A4 *1B genotype, and other influx or efflux transporters such as SLCO1B1, SLCO1A2, ABCC1 (MRP1), ABCC2 (MRP2) and ABCG2 (BCRP). 23 -27 The present study found higher atazanavir concentrations in women versus men, a finding described by others, 28 but women did not have lower weight-adjusted CL/F.…”
Section: Discussionsupporting
confidence: 72%
“…Examples may include variability in the pregnane X receptor (PXR), which controls transcription of CYP3A and ABCB1, the CYP3A4 *1B genotype, and other influx or efflux transporters such as SLCO1B1, SLCO1A2, ABCC1 (MRP1), ABCC2 (MRP2) and ABCG2 (BCRP). 23 -27 The present study found higher atazanavir concentrations in women versus men, a finding described by others, 28 but women did not have lower weight-adjusted CL/F.…”
Section: Discussionsupporting
confidence: 72%
“…Although a 2.4-fold-higher atazanavir AUC was described in women versus men receiving atazanavir along with ritonavir-boosted saquinavir [27], when ritonavir-boosted or unboosted atazanavir is the only PI, no significant gender-related differences in atazanavir pharmacokinetic parameters have been identified [1921,28]. …”
Section: Basic Pharmacology and Pharmacokineticsmentioning
confidence: 99%
“…For the once-daily regimen, 73% patients will have at least one interval of more than 36 h and for the twice-daily regimen, 54% patients will have at least one interval of more than 36 h. Reproduced from [11 ]. ASPIRE I and II were prospective, three-way sequential crossover studies of healthy volunteers that compared the pharmacokinetics of SQV/r with SQV/ATV administered either once daily or twice daily [25]. The goal of these studies was to investigate a potential alternative to RTVboosted protease inhibitor therapy, a dual protease inhibitor regimen combining SQV and ATV.…”
Section: Studies Evaluating Pharmacokinetics Of Protease Inhibitorsmentioning
confidence: 99%